Awareness and Level of Knowledge in Preventing Coronary Heart Disease Among Community Sample - Suarningsih, Ni Kadek Ayu; Suindrayasa, I Made (Journal of A Sustainable Global South; Vol 4 No 1 (2020): February 2020DO - 10.24843/jsgs.2020.v04.i01.p03, 2020)
CHD is ranked number one as a cause of death in non-communicable diseases in Indonesia. The increasing number of people with CHD not only having an impact on mortality rates also an increase in health care needs. Adequate knowledge of the disease contributes to an accurate understanding of the disease and improves adherence to a healthy lifestyle to prevent CHD. This study aims to analyze the awareness and level of community knowledge in preventing CHD. This research was a quantitative research with descriptive analytic method. Awareness and level of knowledge about CHD were evaluated using The Heart Disease Fact Questionnaire. In this study, a total of 60 respondents were obtained through a Cluster Random Sampling in the population of people who have not been diagnosed with CHD in the Village of Timpag, Tabanan Regency, Bali. The main results of this study indicated that awareness and knowledge of the highest risk factors are smoking (89.1%) followed by a factor of high cholesterol (86.6%) and high LDL cholesterol levels (86.3%) and uncontrolled blood pressure (85.9%) and overweight (82.4%). Conversely, risk factors for diabetes (50.7%), HDL cholesterol levels (52.1%), and physical activity (53.5%) received less attention. This study found that the majority of respondents were aware of and have adequate knowledge about CHD risk factors. The results of this study can add information in the development of health promotion materials or policies as an effort to prevent CHD. Further research with a larger population needs to be done to increase public awareness of CHD. Index Terms — Awareness, Coronary Heart Disease, Level of Knowledge